The Bacteria with the Lowest Infectious Dose to cause Meat Food Poisoning - Chagan, Sonal (Journal of Interdisciplinary Science Topics, 2017)
In this paper we will investigate the minimal infectious dose of three different common forms of bacteria that cause meat food poisoning. For E.coli it was found that the infectious dose given the minimal inoculum size of 1 bacterium was 6.28 x1057 bacteria cells. For Campylobacter jejuni the infectious dose was 2.88 x1044 bacteria cells and for Listeria this value was 2.41 x10462. Therefore Campylobacter jejuni was found to have the lowest infected dose that causes the symptoms of food poisoning.